Concept to sale of a healthier snack bar - Rush, E; Parsons, A; Yan, M; Kelleher, J; Brown, D (Ommega Publishers, 2016)
Snacking between meals provides important contribution to dietary intake of key nutrients. There is a need for snack bars that are nutrient dense, have a low glycemic load and increase feelings of fullness and satiety. Over the last three years a branded “Nothing Else” dates and almonds life saver snack bar, without preservatives or additives, has been developed in partnership with a food manufacturer. In June 2015, the final bar, with eight simple ingredients, was first produced by our industry partner to meet the nutritional criteria for a health claim. Shelf-life, glycemic index, effect on appetite and satiety and market demand within retail outlets at the Auckland University of Technology were measured. More than 3000 bars were sold in five months and shelf-life exceeds four months. Anecdotal feedback is positive and new retail outlets are under consideration. Proof-of-concept and proof-of-principle for the feasibility of development of a food product by a University in partnership with the food industry has been shown. The translation of the diverse research skills and understanding found within a University to the production and successful retail of a food product is one small step towards providing a food environment that is supportive of a healthier diet.
Keywords: Branding; Food environment; Glycemic index; Health claims; Satiety; Snacks